A bioplastic-based seed coating improves seedling growth and reduces production of coated seed dust. Issue 3 (4th May 2018) - Accinelli, Cesare; Abbas, Hamed K.; Shier, W. Thomas
ABSTRACT: Although recently introduced, film-coating of agronomic seeds is now widely accepted in modern agriculture as an effective technology for protecting germinating seeds and seedlings. These experiments explored the possibility of using a bioplastic-based formulation to film-coat corn (maize; Zea mays L.) and canola ( Brassica napus L.) seeds, alone and in combination with synthetic pesticides and plant growth-promoting bacteria. The thin bioplastic coat did not affect percent germination or seedling growth. However, incorporating spores of the plant growth-promoting bacterium Bacillus subtilis QST 713 into the bioplastic matrix resulted in a greater elongation of corn and canola seedlings than that of seedlings from untreated seeds. Specifically, stems and roots of seedlings that germinated from corn seeds coated with bioplastic containing spores were 18.0% and 21.4% longer, respectively, than stems and roots from uncoated control seeds. In canola seeds, these values were 19.9% and 20.9% higher for stem and roots, respectively. Incorporating a neonicotinoid insecticide, imidacloprid, and a fungicide, pyraclostrobin, into bioplastic coatings, along with B. subtilis spores, provided results comparable to spores and bioplastic alone. Coated seeds were also evaluated for their potential to generate dust after abrasion testing, using a novel image-based method made possible because seed coatings are typically artificially colored. Abraded seed coat fragments are consequently easily detectable with conventional optical instruments. Corn and canola seeds coated with bioplastic released up to 86.1% and 97.6% less dust during abrasive handling than seeds coated with a commercial seed coating matrix measured by the optical approach described here.